ZNACZENIE ZAUFANIA W TWORZENIU KAPITAŁU SPOŁECZNEGO. EKONOMICZNY I SPOŁECZNY WYMIAR ZJAWISKA - Krzyminiewska, Grażyna (Wydział Prawa i Administracji UAM, 2003)
The author touches upon the problem of the role of trust for social capital and social and economic life. It is indicated that their influence upon the social and economic life becomes a crucial element determining the development potential of the community, pro-social and pro- -economic attitudes of individuals and social groups.
ROLE OF CONFIDENCE IN CREATING SOCIAL CAPITAL IN THE ECONOMIC AND SOCIAL DIMENSION